Trade Liberalization and Employment: Aggregate and Dis-Aggregate Analysis for Pakistan - Farman Ali; Saima Urooge; Uzair Ahmad; Sher Ali (Indus Journal of Social Sciences, 2025)
This study aims to investigate impact of trade on employment in Pakistan. This study tried to disclose that impact of trade on total and sectoral employment over the period of 1994- 2023. Trade elasticity is found positive but insignificant in long-run; however, it is found positive and significant in the short-run. The value of ECT is negative and significant; it also confirms the existence of long-run relationship and convergence of any short-run disequilibrium towards long-run equilibrium. In the second model, Trade elasticity of employment in agriculture sector is estimated. Negative elasticity is reported by the technique in agriculture sector in the long-run but insignificant. The short-run trade elasticity of employment is negative and significant. In the third model, Trade elasticity of employment in industrial sector was founded negative and statistically significant in both the short-run as well as long-run. In the fourth model, Trade elasticity of employment in services sector of the economy is estimated. This model’s result reported that the trade elasticity of employment is negative but insignificant in the long-run. On the basis of the results of the present study it is suggested that trade policies may hurt the domestic structure of labour market. Trade can be used as a catalyst to boosts economic activities, but its impacts could be different on different sectors and different periods. Overall impact may be positive or negative.